Socio-cultural integration of North American Koreans as factor of social well-being; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Vorozhishcheva O. M. Olga Mikhailovna (2017, 2017)
Title screen